PENGARUH KOMPENSASI, KEPEMIMPINAN, DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT PLN (PERSERO) AREA SURAKARTA - Parwoto, Sri Hartono & Istiqomah (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this study was to know the effect of compensation, leadership andwork stress on employees' performance simultaneously and partially. This research is asurvey. The study population were employees of PT PLN (Persero) Area Surakarta withtotaling 120 employees. A sample of 60 respondents with simple random samplingtechnique. The data used are primary data and secondary data. Data collectiontechniques used documentation, questionnaire and literature. Data were analyzed usedmultiple linear regression. The results showed that compensation, leadership and workstress effect on employee performance simultaneously. Compensation has positive effecton employee performance. Leadership has positive effect on employee performance.Work stress has negatively effect on employee performance. Results of determinationcoefficient values obtained Adjusted R2 = 0,533, meaning it can be seen that the effect ofvariable compensation, leadership and work stress affect the performance of employeesis 53,3% while the remaining 46,7% is influenced by other factors not examined, amongothers, the working environment and work discipline. The advice given is that theleadership should give rewards and punishment to the employees, the management needsto provide compensation that takes into account the achievements of employees, fairnessand the ability of the company and increase the benefits others and should managementoffers various training programs or counseling to improve the performance capabilitiesof employees so employees can avoid the stress of work.Keywords: compensation, leadership, work stress, employee performance